Gurson-based incremental damage in fatigue life estimate under proportional and non-proportional loading: Constant amplitude and low cycle regime applications. (August 2020) - Neves, R.S.; Ferreira, G.V.; Malcher, L.
Highlights: Gurson-based model in multiaxial fatigue. Tension/compression mechanism for damage evolution. Multiaxial fatigue life prediction in incremental damage. Proportional and non-proportional loading in constant amplitude. Shear mechanism in combined tension/compression proportional and non- proportional loading. Abstract: This contribution proposes an incremental approach to fatigue life estimate of ductile materials subjected to low cycle fatigue. In this approach, the life prediction is based on the evolution of the internal damage variable of a proposed extension for the Gurson model capable of describing the gradual degradation of the material in function of the number of loading cycles. The extension of the model consists in the inclusion of the Armstrong-Frederick kinematic hardening law [4] and the reformulation of the damage evolution law proposed by Gurson [22], assuming the Nahshon and Hutchinson shear mechanism [43] and a term based on the normalized third invariant with the role to promote asymmetric damage growth under axial (tension–compression) cyclic conditions. An implicit integration scheme is developed, and numerical analyzes are done through simulations at one Gauss point. In this context, the incremental damage approach has applied to experimental data extracted from the literature for thin-walled tubular specimens made of two different materials, S460N structural and hot-rolled normalized SAE 1045 steels. Finally, the predictive capacity of the proposed approach is evaluated comparing predicted and experimentally observed results considering six different proportional and non-proportional loading paths.